Preface to Volume 5, Issue 2 (Trento Student Law Review, 2023)
Dear readers,It is with the utmost privilege that I introduce you Volume 5, Number 2 of the Trento Student Law Review. Once again, this Review aspires to make its modest contribution to the panorama of juridical literature, presenting an Issue in which topics of Comparative, European, and International law, which are all very dear to our Faculty, are discussed.With this eleventh publication, the Trento Student Law Review has published more than fifty articles, a result that should be celebrated since this project has been around only for five years. Allow me to make a brief comment about it.With the end of my mandate, the first generation of editors who have been part of this Review since its first year of existence also ends. My perspective has afforded me the privilege of seeing the work of this Editorial Board from its first volume and participating in its growth.Growing up, this Review has tried to fill a gap and create a wide-ranging environment for students who wanted to participate in the university dimension more actively.Growing up, this Review has allowed almost a hundred editors and aspiring jurists to build the necessary sensitivity and attention to face a world where the law is constantly, and frenetically, evolving. In addition, it has been a meeting point for all those who, in their academic path within this Faculty, have seen in scientific literature and research the keys to be able to improve and learn by doing.Growing up, this Review has tried to be so much more.This has not been an easy path, but despite the times of difficulty, the desire to create a better product has always been a driving force, and the obstacles we have encountered along the way have helped us learn and grow in the right direction.We would not have had this privilege of hoping for the best without the continuous, unwavering support of the Faculty of Law of the University of Trento and its academic community, to whom we extend our deepest gratitude. A further thanks goes to the entire editorial staff of the TSLR, which has managed to work as a real team.Lastly, I wish to express my gratitude to all those who have been part of this Review over the years: your contribution has made this project richer and full of potential.I am confident that the helm is in the right hands with the new Managing Board and Rossella Borella as Director. I wish them all the best for the important new results they will achieve.Ad maiora!